Hadith Regarding the Law of Tabarruk against Habaib: Living Hadith Study of Gedongsari Prambon Nganjuk Islamic Boarding School - Surur, Aziz Miftahus; Sumbulah, Umi (LPPM IAIN Kudus, 2023)
The occurrence of pros and cons regarding the law of Tabarruk practice against Habaib requires hadith research on the direction of Tabarruk. Because to know the law requires an in-depth study of the meaning of the hadith text itself. This study aims to provide readers with an understanding of the importance of understanding the text of the Prophet’s Hadith. In addition, they also know the methods used by classical and contemporary scholars in practicing Hadith. This research is field research with a qualitative approach. Gedongsari Islamic Boarding School, the administrators and the students, are the main objects of this research. The primary source for the research theories is the book al-Jami’ ash-Shahih by al-Bukhari. Several works such as al-Mutashaddidun by Ali Jumah Muhammad, Mafahim Yajibu ‘an Tushahhah by Sayyid Muhammad Alawi, al-Mulakhas fi Syarh Kitab at-Tauhid by Fauzan Salih, and Fath al-Majid Syarh Kitab at-Tauhid by Abd Rahman Hasan Alu Syaikh are considered as the minor sources. The Hadith about Tabarruk is a category of valid Hadith that can be used as evidence. Al-Qur’an and hadiths with the same theme also corroborate the Hadith. In practice, the practice of the Tabarruk tradition that has been attached and rooted in the Gedongsari Islamic Boarding School is not all based on hadith encouragement. However, several factors influence these habits. It cannot be separated from this habit from the dogma that the kiais and teachers have taught.